Visualizing and manipulating phosphoinositide and phospholipid signaling - Prestwich, Glenn (Henry Stewart Talks, 2008)
Making and using phosphoinositide phosphate (PIP) affinity probes, Effects of exogenous PIPs, Metabolically-stabilized PIPs, New tethering strategies, Signaling proteomics, Antibodies to PIPs, Visualizing phospholipase A and D activity with fluorogenic probes
Reviewed at 2022/04/12